A nasal hypertrophic lesion as a presentation of herpes simplex virus. (2019) - Chiu, Chia-Yu; Randhawa, Gurchetan; Nada, Khaled; Tomczak, Ewa; Feinstein, Addi; Hennessey, Karen
Abstract: Herpes simplex virus type 1 and type 2 (HSV-1 & HSV-2) are one of the leading causes of ulcer and blister lesions worldwide. These infections are latent with recurrences but many people may have a seropositive antibody yet remain asymptomatic. Although HSV presenting with hypertrophic lesions have been reported in the literature at urogenital, lung, and conjunctival sites, we describe a case of a mass lesion in the nasal cavity of a 46 year-old female with a history of human immunodeficiency virus (HIV). The patient presented initially with nasal congestion and subsequently developed facial edema. The mass lesion regressed after one month of treatment with valacyclovir.